2016
DOI: 10.1111/cmi.12543
|View full text |Cite
|
Sign up to set email alerts
|

Development of an in vitro colonization model to investigateStaphylococcus aureusinteractions with airway epithelia

Abstract: SUMMARY Staphylococcus aureus is a bacterial pathogen responsible for a wide range of diseases and is also a human commensal colonizing the upper respiratory tract. Strains belonging to the clonal complex group CC30 are associated with colonization, although the colonization state itself is not clearly defined. In this work, we developed a co-culture model with S. aureus colonizing the apical surface of polarized human airway epithelial cells. The S. aureus are grown at the air-liquid interface to allow an in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 63 publications
(127 reference statements)
1
29
0
Order By: Relevance
“…We and others have observed that the S. aureus agr genes are repressed during nasal colonization (Burian et al, 2010; Kiedrowski et al, 2016; Tulinski et al, 2014), but staphylococcal skin colonization has comparatively received less attention at the mechanistic level. Using a porcine skin explant model, we demonstrated that S. epidermidis requires quorum sensing to successfully colonize (Olson et al, 2014), suggesting the regulatory system is important for survival in this environment.…”
Section: Discussionmentioning
confidence: 96%
“…We and others have observed that the S. aureus agr genes are repressed during nasal colonization (Burian et al, 2010; Kiedrowski et al, 2016; Tulinski et al, 2014), but staphylococcal skin colonization has comparatively received less attention at the mechanistic level. Using a porcine skin explant model, we demonstrated that S. epidermidis requires quorum sensing to successfully colonize (Olson et al, 2014), suggesting the regulatory system is important for survival in this environment.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have addressed these aspects only partially either by focusing on the internalized bacteria only, or over only fairly short periods of time post infection (p.i.) (11,12,(14)(15)(16)(17). Yet, it is important to get the 'complete picture' of such an infection scenario, because the invasion and destruction of lung epithelial cells is representative for some of the most serious staphylococcal diseases possible, especially necrotizing pneumonia.…”
Section: Downloaded Frommentioning
confidence: 99%
“…In the case of S. aureus, how quorum-sensing kinetics are controlled in ways that best suit the commensal lifestyle is unclear, and gaining insight into this dynamic may be particularly challenging given the profusion of inflammatory and tissue-damaging secreted virulence factors made by this pathogen. Although colonization studies (7,85) demonstrate that agr is repressed in this state, and as outlined above, many studies indicate that numerous host factors (e.g. serum components, ROS, low pH) are capable of repressing agr function, the reference state for these studies was growth under idealized laboratory culture conditions.…”
Section: Challenges In the Field And Future Perspectivesmentioning
confidence: 99%
“…The fact that S. aureus can colonize without harming the host is somewhat surprising considering the depth of secreted virulence factors produced by this pathogen (3,7,8). These include an impressive array of pore-forming toxins, degradative enzymes, superantigens, and other immunostimulatory exoproteins.…”
mentioning
confidence: 99%